SPECIAL NEEDS CHILDREN NUTRITIONAL STATUS WITH GROSS MOTOR DELAY AGE 0-6 YEARS: AN OVERVIEW - Swiny Anniza; Rini Andriani; Patricia Elfira Vinny (Indonesian Journal for Health Sciences, 2022)
Malnutrition and disability are major global health problems. Malnutrition can cause to a variety of disabilities, and disability can contribute to malnutrition. This study aims to overview of special needs children nutritional status with gross motor delay age 0-6 years in the Regional Psychiatric Hospital of Sungai Bangkong. The design of this study was a cross-sectional descriptive study on 54 children with special needs in Psychiatric Hospital Sungai Bangkong Pontianak. The results showed that special needs children nutritional status in Down Syndrome is normal (63,7%), severely wasted (9,1%), wasted (27,3%). Cerebral Palsy obtained (50,0%) normal, wasted (33,3%), severely wasted (16,7%). Gross motor delay is (63,0%) normal, (14,8%) wasted, (3,7%) severely wasted, (11,1%) are possible risk of overweight, (3,7%) overweight, (3,7%) obesity. ADHD have normal nutritional status (100%). PDD NOS have wasted (33,3%), normal (33,3%), overweight (33,3%). This shows conclusion that red flag, risk factor of children before, during, after birth and maternal risk will influence nutritional status and gross motor development.